2013
DOI: 10.1111/ejn.12249
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction alleviates the age‐related decrease in neural progenitor cell division in the aging brain

Abstract: Production of new neurons from stem cells is important for cognitive function, and the reduction of neurogenesis in the aging brain may contribute to the accumulation of age-related cognitive deficits. Restriction of calorie intake and prolonged treatment with rapamycin have been shown to extend the lifespan of animals and delay the onset of age-related decline in tissue and organ function. Using a reporter line in which neural stem and progenitor cells are marked by the expression of GFP, we examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 43 publications
6
59
0
2
Order By: Relevance
“…In the light of recent findings that prolonged exposure to DR increases both the total number of dividing and progenitor cells in the dentate gyrus, the neurogenesis niche in adult rats (Couillard-Despres et al 2011;Park et al 2013), the abovementioned properties of desmosterol may suffice to increase the pool of membrane-active brain sterols. Furthermore, in DHCR24 −/− (24-dehydrocholesterol reductase) mice lacking cholesterol, desmosterol accounts for 99 % of the total sterols, indicating that this precursor takes over the function of cholesterol despite differences in their biophysical and functional properties (Wechsler et al 2003;Vainio et al 2006).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the light of recent findings that prolonged exposure to DR increases both the total number of dividing and progenitor cells in the dentate gyrus, the neurogenesis niche in adult rats (Couillard-Despres et al 2011;Park et al 2013), the abovementioned properties of desmosterol may suffice to increase the pool of membrane-active brain sterols. Furthermore, in DHCR24 −/− (24-dehydrocholesterol reductase) mice lacking cholesterol, desmosterol accounts for 99 % of the total sterols, indicating that this precursor takes over the function of cholesterol despite differences in their biophysical and functional properties (Wechsler et al 2003;Vainio et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…This could be attributed, at least in part, to neurogenesis that takes place in the adult dentate gyrus (Couillard-Despres et al 2011). Accordingly, the DR-induced increase in desmosterol concentration in the aging hippocampus could at least in part correlate with the increased number of progenitor cells differentiating into neurons following DR (Park et al 2013). Furthermore, the different responses of the key proteins involved in cholesterol homeostasis in the cortex and hippocampus to DR reported herein could be attributed to the specific requirements for cholesterol in different brain regions Trapani and Pallottini 2010;Segatto et al 2012;Perovic et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, we and others have reported that DR promotes neurogenesis [29], enhances plasticity [30,31], and retards ageassociated brain functional impairments [32][33][34]. The exceptionally diverse anti-aging and neuroprotective properties of DR are probably linked to its ability to recruit adaptive cellular stress responses and to modulate the neuroendocrine system both of which are impaired in aged animals.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, the use of reporter mice enables efficient dissection of the neuronal differentiation cascade in the DG into distinct steps and assembly of a detailed scheme of entire cascade (Encinas et al 2006(Encinas et al , 2011bEncinas and Enikolopov 2008). As a following step, this scheme can be used to determine the classes of stem and progenitor cells in the DG that are affected by various pro-and antineurogenic factors and stimuli (for examples of such analyses, see Encinas et al 2006Encinas et al , 2011aPark et al 2013).…”
Section: Using Reporter Lines To Dissect Neuronal Differentiation Casmentioning
confidence: 99%